Motivations of South African physicians specialising in public health - Virginia Elizabeth Melvill Zweigenthal; William M. Pick; Leslie London (Taylor & Francis Group, 2018)
Background: South African physicians can specialise in public health through a four-year 'registrar' programme. Despite national health policies that seemingly value public health (PH) approaches, the Public Health Medicine (PHM) speciality is largely invisible in the health services. Nevertheless, many physicians enrol for specialist training. Objectives: This study investigated physicians' motivations for specialising in PHM, their intended career paths, perceptions of training, and perspectives about the future of the speciality. Methods: Focus groups and in-depth interviews were conducted with specialists-in-training and newly qualified specialists, and thematic analysis of transcripts was performed. Results: Motivations, often driven by difficult experiences as young physicians in poorly resourced clinical settings, stemmed from a commitment to improving communities' health and desire to impact on perceived failing health systems. Rather than 'exiting' the South African health service, selecting PHM specialist training enacted participants' 'loyalty' to population health. Participants anticipated carving out their own careers due to an absence of public sector career paths. They believed specialists' contribution centred on providing 'public health intelligence' - finding and interpreting information; supporting services through management and leadership; and inputting into policymaking and planning. Conclusions: Competencies of PHM specialists should be refined to inform and improve management of this scarce human resource for health. This is particularly important given the proposed major health reforms towards universal health coverage in South Africa presently. In addition, findings highlight the importance of physicians' early work experiences where avenues for expressing 'voice', mediated by 'loyalty', could be utilised to improve public sector health systems.